DWI of Autoimmune Pancreatitis: Is It an Imaging Biomarker for Disease Activity? - Zhu, Liang; Zhang, Wen; Jin, Zhengyu; Sun, Zhaoyong; Xue, Huadan; Denecke, Timm; Hamm, Bernd; Lv, Hong; Zhang, Shengyu; Lai, Yamin (American journal of roentgenology (1976), 2021)
The purpose of this article was to evaluate the DWI features of autoimmune pancreatitis (AIP) at baseline, under treatment, and at relapse, and to assess the diagnostic accuracy of the ADC for determining disease activity. This retrospective study was approved by the institutional review board. Sixty-two patients with AIP (48 at initial attack and 14 at relapse) underwent MRI with DWI (b = 0 and 800 s/mm ) at 3 T before receiving corticosteroid therapy (CST) and during follow-up. Seventeen patients had disease relapse during follow-up, whereas the others remained clinically stable. Forty age- and sex-matched patients without pancreatic disease served as the control group. The ADC value of AIP at baseline was significantly lower than that for a disease-free pancreas (0.99 ± 0.12 vs 1.26 ± 0.10 × 10 mm /s, < .001). Under CST, the ADC value increased gradually at the short-term and long-term follow-up (1.16 ± 0.12 and 1.23 ± 0.12 × 10 mm /s, respectively, both < .001). At relapse, the ADC had a relative decrease (1.11 ± 0.20 × 10 mm /s) but was significantly higher compared with the initial attack ( = .003). The AUC of ADC serum IgG4 level at ROC analysis for baseline versus clinically stable AIP was 0.867 and 0.700, the AUC for clinically active AIP versus clinically stable AIP was 0.762 and 0.686, and the AUC for relapsed AIP versus clinically stable AIP was 0.648 and 0.669. DWI reflected the dynamic change of AIP under CST, and the ADC value for DWI outperformed the serum IgG4 value for determining disease activity. However, relapsed disease showed less diffusion restriction, and the ADC value was less accurate for predicting relapse.